The role of structural funding for stability in the German banking sector - Fabian Schupp; Leonid Silbermann (Deutsche Bundesbank, 2017)
We analyze whether, and if so by how much, stable funding would have contributed to the financial soundness of German banks in the time period between 1995 and 2013, before the Basel III liquidity regulation to address excessive maturity mismatches in the wake of the financial crisis via the Net Stable Funding Ratio can be expected to have been fully implemented. Using a dataset that contains information on critical events of German banks, we find that financing loans using fewer customer deposits would have been associated with a higher probability of financial distress for savings banks and credit cooperatives. A one percent rise in the loanto-deposit ratio from 1995 to 2013 corresponds to an increase in the probability of experiencing a critical event, implying approximately two additional savings banks and two additional credit cooperatives in financial distress. No such effect can be detected for commercial banks (excluding big banks), which are found to be far more heterogeneous with respect to their business models.
Keywords: G21; G28; C23; C25; 330; banks; financial distress; stable funding; Basel III liquidity regulation; NSFR; financial stability; panel data; random effects logit